Peculiarities of Clinical and Hemodynamic Manifestations of Migraine Strokes - Sanoeva, Matlyuba; Saidvaliyev, Farukh; Rakhimbayeva, Gulnara; Gulova, Munisakhon; Avezova, Mekhriniso (International Journal of Psychosocial Rehabilitation, 2020)
Migraine often causes strokes among patients under 50 years of age in 1 to 17% of cases, and repetitive migraine paroxysms lead not only to chronic migraine but also to vascular complications of the brain. Often, diagnoses of “dumb heart attacks”, “iatrogenic strokes”, and “strokes of unknown etiology”, which are the result of severe migraine crises resulting in dumb subcortical heart attacks and persistent leukoencephalopathy, can still be seen in practitioners’ diagnoses. The aim of the study was to study the clinical and hemodynamic features of migraine strokes. The study examined 84 (100%) patients, 52 (61.9%) with migraine strokes (1-major group) and 32 (38.1%) with ACVD against the background of HD (hypertension disease) and A (atherosclerosis) (2-comparative group). Clinical-neurological studies, EEG and TСDSs of brain vessels were carried out, the coma scales of Glazko, Scandinavian and American (NIHSS) three-dimensionalscales (VRS, NRS, VAS) and facial pain scales FPS, IDmigraine and MIDAS were used. Patients with migraine stroke were observed to have a severe condition with a sudden and rapid clinical course, acute onset against the background of regular migraine attacks, due to the typical vascular type of migraine, caused by dystonia of the brain vessels. Migraine strokes and ACVD against the background of HD and A, having different etiopathogenic factors of the disease development, lead to the formation of the same pathological link, i.e. the zone of ischemic focus in the brain with all its neurological manifestations and complications, which ultimately require close attention, differentiated approach and timely correction. The choice of preventive and restorative therapy of migraine strokes should be directed towards the elimination of cause-effect factors of disease formation, because only in this case it is possible to mediate persistent, prolonged manifestations of the disease in the form of motor, sensitive, psychopathological, cognitive and vegetative disorders.